2021
DOI: 10.3390/cells10102755
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Renin-Angiotensin-System Alterations in COVID-19

Abstract: The renin-angiotensin system (RAS) plays a pivotal role in a wide series of physiological processes, among which inflammation and blood pressure regulation. One of its key components, the angiotensin-converting enzyme 2, has been identified as the entry point of the SARS-CoV-2 virus into the host cells, and therefore a lot of research has been devoted to study RAS dysregulation in COVID-19. Here we discuss the alterations of the regulatory RAS axes due to SARS-CoV-2 infection on the basis of a series of recent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 125 publications
(211 reference statements)
1
30
1
1
Order By: Relevance
“…1 ) ( 7 ). Ang II acts via the Ang II type-1 receptor (AT 1 R) to induce vasoconstriction, inflammatory cytokine production, and extracellular matrix synthesis ( 8 ). Ang II also stimulates adrenal aldosterone production, leading to sodium and fluid retention and an increase in blood pressure ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 ) ( 7 ). Ang II acts via the Ang II type-1 receptor (AT 1 R) to induce vasoconstriction, inflammatory cytokine production, and extracellular matrix synthesis ( 8 ). Ang II also stimulates adrenal aldosterone production, leading to sodium and fluid retention and an increase in blood pressure ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding Ang-(1−7) levels in COVID-19 patients, some reports have shown an increase [6] , [10] , [27] while others a decrease or no change [11] , [19] , [28] . Thus, despite the fact that COVID-19 is associated with an increased ACE2 [6] , [7] , [8] , [9] , [16] , [29] , conflicting results were reported regarding Ang II and Ang-(1−7) levels [30] . Our work showed that even sACE2 activity was increased, the ratio Ang-(1−7)/Ang II was not changed in the plasma of COVID-19 patients, reflecting that the rate of conversion of Ang II into Ang-(1−7) was not modified.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ang-(1−7) can be formed not only from Ang II but also from Ang I. Neutral endopeptidase (EC 3.4.24.11, EP 24.11), neprilysin, thimet oligopeptidase (EC 3.4.24.15) and prolyl oligopeptidase (EC 3.4.21.26) cleave the bond at residues Pro 7 -Phe 8 of Ang I, thus generating Ang-(1−7) [30] , [33] . In fact, COVID-19 is associated with low circulating plasma levels of Ang I and Ang-(1−7) [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Because SARS‐CoV‐2 depends on the use of host cell facilities for survival and replication, understanding host–cellular functions used by the virus would be essential. Given the advances in this area, scientists suggest that the Renin‐Angiotensin System (RAS) and the p38 mitogen‐activated protein kinase (p38 MAPK) pathway are promising targets for the treatment of COVID‐19 (Dean et al, 2021 ; Grimes & Grimes, 2020a ; Pucci et al, 2021 ; Sohag et al, 2020 ). Accordingly, the use of modulators of such cellular pathways is attracting great attention for the treatment of COVID‐19 (Valipour et al, 2021 ).…”
Section: Figurementioning
confidence: 99%